2021
DOI: 10.1680/jgeot.19.p.042
|View full text |Cite
|
Sign up to set email alerts
|

Seismic harmonic response of inhomogeneous soil: scaling analysis

Abstract: The study of the seismic response of inhomogeneous soil deposits, underlying rigid bedrock, has traditionally been framed as a one-dimensional wave propagation problem in a linear viscoelastic medium. When it comes to modelling soil inhomogeneity, the current trend to model the continuous variation of soil stiffness with depth employs a ‘generalised parabolic function’. Exact solutions have already been obtained, but these come in terms of Bessel functions, which muddle the interpretation of results and obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Likewise, an estimate particularly well-suited for the high-frequency regime has been furnished previously by the authors [15]. Regarding the ground surface amplification relative to the profile base, it was found…”
Section: Previous Results By Garcia-suarez Seylabi and Asimaki (2019)mentioning
confidence: 68%
“…Likewise, an estimate particularly well-suited for the high-frequency regime has been furnished previously by the authors [15]. Regarding the ground surface amplification relative to the profile base, it was found…”
Section: Previous Results By Garcia-suarez Seylabi and Asimaki (2019)mentioning
confidence: 68%
“…In a previous work [Garcia-Suarez et al, 2020], the authors focused on a specific, commonly used, distribution of S-wave velocity, the so-called "generalized parabola" (density is assumed to be constant):…”
Section: Previous Resultsmentioning
confidence: 99%
“…This work has been occupied, chiefly, with a generalization of previous results obtained under the assumption of S-wave velocity profile abiding by eq. (2) [Garcia-Suarez et al, 2020] to any profile meeting two simple requirements: 1) continuity and boundedness of first derivative of f (η), 2) positive (non-zero) values of c s throughout the deposit, including at the free-surface. It has been shown that this result stems from a classical result in Physics, the so-called Geometrical Optics approximation.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in previous work by the authors [10][11][12], coming up with equivalent homogeneous properties valid over the whole frequency range appears an irreducible task. Instead, it seems more feasible to assess equivalent homogeneous properties for either the fundamental mode [10], or relatively high frequencies in general [11].…”
Section: Equivalent Homogeneous Propertiesmentioning
confidence: 96%